Combination of Terrestrial and Satellite Gravity Data for the Characterization of the Southwestern Coastal Region of Cameroon: Appraisal for Hydrocarbon Exploration - Paul Gautier Kamto; Willy Lemotio; Alain-Pierre Kamga Tokam; Loudi Yap (International Journal of Geophysics)
The southwestern coastal region of Cameroon is an area of interest because of its hydrocarbon potential (gas and oil). Terrestrial and satellite gravity data were combined and analyzed to provide a better precision in determining the structure of the study area. Firstly, the two gravity databases (in situ and satellite) have been coupled and validated using the least square collocation technique. Then, spectral analysis was applied to the combined Bouguer anomaly map to evaluate the thickness of sediments in some localities. We found that the sedimentary cover of the southwestern coastal region of Cameroon has a thickness that varies laterally from 1.68±0.08 to 2.95±0.15 km, especially in the western part. This result confirms that our target area is a potential site for hydrocarbon exploration. The horizontal gradient method coupled with the upward continuation at variable heights has been used to highlight several lineaments and their directions (N-S, E-W, SW-NE, and SSW-NNE). Lineaments trending in an N-S orientation are predominant. The Euler deconvolution method was also applied to the Bouguer anomaly map to determine the position, orientation, and depth of the different superficial faults of the study area. It appears that the majority of superficial faults have an N-S and SSW-NNE orientation. These directions are correlated with those previously highlighted by the maxima of horizontal gradient. The structural map could be used for a better identification of the direction of fluid flow within the subsurface or to update the geological map of our study area.